Evaluating interventions to reduce child marriage in India - Bruce Rasmussen; Neelam Maharaj; Anup Karan; John Symons; Sakthivel Selvaraj; Rajeev Kumar; Margarita Kumnick; Peter Sheehan (Journal of Global Health Reports)
# Background This paper estimates the costs and benefits of investing in education interventions and specific child marriage programs to reduce child marriage in India. Child marriage in India remains highly prevalent despite considerable progress in the last decade or more, associated, in particular, with a decline in poverty. The economic consequences of the COVID 19 pandemic are likely to reverse these gains, meaning that the interventions to reduce child marriage evaluated in this paper assume even greater importance.